Change points and temporal dependence in reconstructions of annual temperature: Did Europe experience a little ice age? - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2012)
We analyze the timing and extent of northern European temperature falls during the Little Ice Age, using standard temperature reconstructions. However, we can find little evidence of long swings or structural breaks in European weather before the twentieth century. Instead, European weather between the fifteenth and nineteenth centuries resembles uncorrelated draws from a distribution with a constant mean (although there are decades of markedly lower summer temperature); with the same behaviour holding more tentatively back to the twelfth century. Our results suggest that the existing consensus about a Little Ice Age in Europe may stem from a Slutsky effect, where the standard climatological practice of smoothing data before analysis gives the spurious appearance of irregular oscillations.
Keywords: 330